Location-Optoelectronic Property Correlation in ZnO:Al Thin Film by RF Magnetron Sputtering and Its Photovoltaic Application - Fang-I Lai (MDPI AG, 2021)
In this study, a radio-frequency magnetron sputter system was used to deposit Al2O3 doped ZnO (AZO) thin films at room temperature, and the soda lime glass (SLG) substrates were placed at different zones relative to the center of the sample holder under the target. The samples were then analyzed using an X-ray diffractometer, Hall-effect measurement system, UV-visible spectrophotometer, and X-ray photoelectron spectroscopy. It was found that the electrical, structural, and optical properties of AZO films strongly depend on the target racetrack. The AZO thin film grown at a location outside the racetrack not only has the most suitable figure of merit for transparent conductive films, but also retains the least residual stress, which makes it the most suitable candidate for use as a CZTSe transparent conductive layer. When applied to CZTSe solar cells, the photoelectric efficiency is 3.56%.